The normativity of (digital) sociality - Pirc, Gašper (Monitor ISH, 2023)
In the paper, I investigate the proposition that mutuality is something that coexists with or even precedes human individuation as it can be questioned at the advent of virtualized societies. By critically assessing the fundamental (social) ontology of Jean-Luc Nancy that regards human sociality as fundamental to any human development and provides ontological grounding for his philosophy of mutual bond. Nevertheless, I am also wary of the potential problems due to the normative lack of ontological assessment of mutuality, especially in the light of changes during the time of ever-faster digitalization and the rise of virtual societies. To better assess both the question of sociality as a key feature of human development and the normative potential in it, I both offer additional theories of mutual bond and expound upon the prospect of yet unrealized metaverse – a virtual society that is being predicted and actively worked on in recent years – that may have the potential to change the way we understand what the premises of human sociality are and how the development of technology may transform the way we see what distinctive features of human existence are.
Keywords: Cavell; metaverse; metaverzum; Nancy; philosophy; socialna filozofija; Tomasello; Tomasselo; virtual reality; virtualna resničnost